THE ANALYSIS OF FACTORS AFFECTING TOURISM INDUSTRY AND ITS IMPLICATION TOWARD ECONOMIC GROWTH, EMPLOYMENT OPPORTUNITY, INCOME PER CAPITA, LOCAL INCOME AND LEVEL OF POVERTY (A Study in Nusa Tenggara Timur) - Daniel Mutis (Universitas Trisakti, 2012)
The background phenomenon of the tourism industry problem in East Nusa Tenggara was low compared to its potential realization of the tourism industry and the welfare of the area that has not been optimal. How to influence the tourism ir.dustry in the area of East Nusa Tenggara and how the tourism industry also influences the welfare of the area. The research objective was to obtain empirical evidence and assess the linkages between economic phenomena on the influence of government assistance, infrastructure, education, tourism industry, tourism products, credit linkages, public attitudes on tourists, and tourism user satisfaction of the tourism industry and its implications on economic growth, employment, income per capita, the PAD and the level of poverty as a landmark study in the area of East Nusa. Study sample is limited to I5 districts / cities that do not have the regional growth during the period of 5 years in East Nusa Tenggara. The techniques analysis of this research using path analysis. The study concluded that the factors are investigated Simultaneously have a significant effect on the tourism industry. Partially, government assistance has an influence domain. The tourism industry is more affected by direct and indirect influence of other factors. It also concluded that the tourism industry significantly influence economic growth and employment, but not against income per capita, PAD, and the level of poverty. Advised to the government to encourage synergy and quality of the factors studied Especially government aid Government needs to develop. tourist infrastructure that facilitate accessibility to tourist sites. In addition to improving the quality and quantity of tourism products, tourism education tourism industry players also need to be tailored to the characteristics of tourist attractions and served Bureaucracy in order to facilitate credit and lending their effectiveness monitored The tourism industry needs to be maintained as labor-intensive economic sectors that contribute to economic growth. The government also advised to encourage the growth of economy higher than population growth, empower the tourism industry as a source of local revenue, and increase employment opportunities and income distribution for low-income communities.